Removal of Fluorescein Dye from Aqueous Solutions Using Natural and Chemically Treated Pine Sawdust - Nada S. Al-Kadhi (International Journal of Analytical Chemistry)
The various factors affecting the removal of fluorescein dye using sawdust from aqueous solutions such as time, initial concentration, pH, and temperature were studied. The optimal conditions for removing the FD are 1 g of sawdust at pH 3 and 120 min time of contact. Dye removal dropped from 93.42% to 80.04% with natural pine sawdust (NPS) and from 96.83% to 81.51% with synthetic pine sawdust (SPS) by increasing their concentration from 2 to 10 mg/L. Isotherm, kinetic, and thermodynamic models were applied for determining their constants. The results indicated that the FD removal equilibrium was effectively defined by the Langmuir, Freundlich, and Temkin models. Kinetic studies showed that the pseudo-second order was well suited for dye removal, and the internal diffusion process was by two steps. The thermodynamic parameter values suggested that FD removal were physical adsorption, exothermic, lower randomness, and spontaneous.